Correlation Between the Phases of Tuberculosis Treatment and Depression Levels - Reinhart Nathaniel Loasari; Anita Dahliana; Katharina Merry Aprilliani Angkawidjaja (Jurnal Penelitian Pendidikan IPA, 2025)
Tuberculosis (TB) is an infectious disease that remains a global health problem, including in Indonesia. In addition to the physical impact, pulmonary TB patients are also susceptible to psychological disorders such as depression, which may arise due to concerns about symptoms and treatment. Depression ranks first among mental health disorders in Indonesia. This study aims to determine the correlation between the phases of TB treatment and depression levels in pulmonary TB patients. This study employed an analytical observational design with a cross-sectional approach and used consecutive sampling. Data were collected from February 17 to June 8, 2024, using the Beck Depression Inventory-II (BDI-II) questionnaire. A total of 38 pulmonary TB patients participated in this study with 6 experiencing depression of varying severity. Spearman correlation test showed no statistically significant association between the phases of TB treatment and depression levels (p= 0.093). Based on these results, it can be concluded that there is no significant correlation between the phases of TB treatment and depression levels in pulmonary TB patients at Puskesmas Putat Jaya, Surabaya.